Enhancement of the scheduling algorithm (software and interfacing development)/ Zuraini Ab Rashid - Ab Rashid, Zuraini (1996)
Batch production is used throughout the process industries for the manufacture of fine chemical, plastic, pharmaceutical, paints, ceramics and cosmetics. The batch process is economically desirable whenever a complex product quantity is small but the product value or product demand is very high. This research work describe the enhancement of scheduling algorithm of batch process using shortest path and k th shortest path. By using turbo pascal programming language, the software developed a menu driven gharahical tool to become more powerful and attractive for simulation schedule and interfacing to justify the finding. The PCL-812 is used as an I/O board for interfacing with LED as a node or activity.